Advances in research on the anti-tumor mechanism of Astragalus polysaccharides - Yang, Qian; Meng, Dandan; Zhang, Qinyuan; Wang, Jin (Frontiers in Oncology, 2024)
The dry root of the soybean plant Astragalus membranaceus (Fisch) Bge. var. mongholicus (Bge) Hsiao or A. membranaceus (Fisch) Bge, Astragali Radix (AR) has a long medicinal history. Astragalus polysaccharide (APS), the natural macromolecule that exhibits immune regulatory, anti-inflammatory, anti-tumor, and other pharmacological activities, is an important active ingredient extracted from AR. Recently, APS has been increasingly used in cancer therapy owing to its anti-tumor ability as it prevents the progression of prostate, liver, cervical, ovarian, and non-small-cell lung cancer by suppressing tumor cell growth and invasion and enhancing apoptosis. In addition, APS enhances the sensitivity of tumors to antineoplastic agents and improves the body’s immunity. This macromolecule has prospects for broad application in tumor therapy through various pathways. In this article, we present the latest progress in the research on the anti-tumor effects of APS and its underlying mechanisms, aiming to provide novel theoretical support and reference for its use in cancer therapy.